Digital divide, globalization and income inequality in sub-Saharan African countries: Analysing cross-country heterogeneity - Hermann Ndoya; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The aim of this paper is to analyse the impact of digital divide on income inequality in subSaharan Africa over the period 2004-2016. In applying a finite mixture model (FMM) to a sample of 35 sub-Saharan African (SSA) countries, this study posits that digital divide affects income inequality differently. Our findings show that the effect of digital divide on income inequality varies across two distinct groups of countries, which differ according to their level of globalization. In addition, the study shows that, most globalized countries are more inclined to be in the group where the effect of digital divide on income inequality is negative. The results are consistent to several robustness checks, including alternative measures of income inequality and additional control variables. The study complements that extant literature by assessing linkages between the digital divide, globalization and income inequality in sub-Saharan African countries contingent on cross-country heterogeneity.
Keywords: C14; O15; O33; O55; 330; Digital Divide; Income Inequality; Globalization; Finite Mixture model